Lower C/N ratio induces prior utilization of soluble microbial products with more dramatic variability and higher biodegradability in denitrification by strain YSF15. (September 2021) - Zhang, Shuai; Ali, Amjad; Su, Junfeng; Huang, Tinglin; Zheng, Zhijie; Wang, Yue; Li, Min
Graphical abstract: Highlights: Low C/N induced strain YSF15 to utilize SMPs as carbon source in the first 12.0 h. Low C/N activated the extracellular metabolism with dramatic change in protein. More degradable matter existed in MW SMPs of 100–3 kDa induced by low C/N. Most of PS in each SMPs fraction was degraded versus PN with less degradability. Abstract: The emphasis of this study lies in how strain SYF15 regulates molecular weight (MW) fractions of soluble microbial products (SMPs) in response to low carbon to nitrogen (C/N) ratio, with high denitrification performance (over 99%). Results indicated SMPs with MW >100 and <50 kDa undoubtedly participated in denitrification before 12.0 h in C/N = 2.0, while sodium acetate was preferred in C/N = 5.0, indicating strain YSF15 was induced to degrade SMPs as a carbon source in low C/N. Additionally, lower C/N activated the extracellular metabolism, with increased fluorescence regional integration (FRI) volume amplitude by 48.08 and 53.43% (versus C/N = 5.0) in MW = 50–10 and 10–3 kDa, respectively. The FRI volume of proteins yielded greater with more degradable components than higher C/N in MW = 100–3 kDa, whereas polysaccharide and protein concentrations differed little with considerable biodegradability, implying components inside protein changed dramatically. This pioneering work contributed to the understanding of denitrification with carbon source deficiency.